HUBUNGAN PANJANG BOBOT DAN INDEKS KEMATANGAN GONAD IKAN TEMBANG (Sardinella fimbriata) DI PERAIRAN PANTAI LABU KABUPATEN DELI SERDANG SUMATERA UTARA - Cherin Monalisa S; Hasan Sitorus; Ani Suryanti (AQUACOASTMARINE, 2016)
The objective of the research was to determine the growth and reproduction aspects based on relationship between of length weight and Gonad Maturity Index (IKG) of Fringescale Sardine (Sardinella fimbriata). The research had been conducted in Labu coastal water, Deli Serdang District of North Sumatera Province for 3 (three) months starting from November 2014 until January 2015. The result are expected to be a source of information that useful for fish resource management to gain the optimal and sustainable utilization.The number of fish samples was 270 fishes which consist of 119 female fishes and 151 male fishes. The result showed that the length range of female fishes was larger than male fishes. Female fish growth pattern was isometric, and male fish was negative allometric.Conditions factor and IKG of female fish was larger than male fish. The correlation of length weight with IKG of fish was strong.Keywords : Length Weight, IKG, Tembang Fish, Labu Coastal Waters.